Fan flaps for Cheiloplasty (lower lip reconstruction): A two year experience - Sheeja Rajan; Saramma Varughese; Jagadeesh S (Indian Journal of Plastic Surgery)
Aim: To evaluate the fan flaps done during the past two years with regard to applicability, reliability, functional perspective and complications. Materials and Methods: All the fan flaps done were reviewed by inspecting case records and directly following up the patients (at periodic intervals). The indications, applicability to defect size, postoperative aesthetic and functional results and drawbacks were noted. Results: Eight fan flaps were done during this period. All were done for squamous cell carcinoma affecting lower lip. All the flaps survived. Two early cases of Gilles fan flap developed significant microstomia. Later flaps with neurovascular preservation maintained sensations with good commissural competence. Nakajima fan flaps gave good overall results. Conclusions: The fan flaps, especially the Nakajima modification with neurovascular preservation are safe and reliable flaps for lip reconstruction in terms of form and function.